La arquitectura escolar pública en Cantabria (1857-1970) - Cabieces Ibarrondo, María Victoria (Artigrama, 2019)
ResumenLa arquitectura escolar pública del siglo XIX en Cantabria apenas contó con edificios singulares promovidos por los ayuntamientos, salvo las escuelas de Terán en Cabuérniga con proyecto de Pueyo firmado en 1861. Las fundaciones, especialmente de indianos y jándalos, fueron las que levantaron magníficas construcciones. En la segunda mitad del siglo, el arquitecto provincial Alfredo de la Escalera redactó numerosos proyectos al carecer los municipios de arquitecto. A finales del XIX y principios del XX, ante la precariedad de los locales existentes, se abordó la construcción de escuelas municipales, destacando los proyectos de Eladio de Laredo en Castro Urdiales, Emilio de la Torriente en Ampuero y Gonzalo Bringas en Colindres. El impulso más importante se produjo en la Dictadura de Primo de Rivera y en la Segunda República en todo el territorio, con proyectos de Javier González-Riancho para Santander y de Deogracias Mariano Lastra y Manuel Vías para Torrelavega, así como de otros arquitectos locales y de la OTCE. Durante el franquismo se construyeron escuelas con proyectos-tipo gracias al llamado Plan Tena.AbstractThe nineteenth-century State Schools architecture in Cantabria barely had unique buildings promoted by Town Halls, except for Terán schools in Cabuérniga, which follow a project signed by Pueyo in 1861. The Foundations, especially those sponsored by Indianos and Jándalos, were the ones that had magnificent buildings raised. In the second half of the century, County architect Alfredo de la Escalera designed numerous projects, as there weren’t Council architects. At the end of the 19 th century and the beginning of the 20 th, faced with the scarcity of schools, the Councils decided to build Council Schools. Among them, those that stand out are the pro-jects designed by Eladio de Laredo in Castro Urdiales, Emilio de la Torriente in Ampuero and Gonzalo Bringas in Colindres. The most important boost took place during Primo de Rivera’s Dictatorship and in the Second Republic in all the area, with projects by Javier González-Riancho for Santander, and by Deogracias Mariano Lastra and Manuel Vias for Torrelavega. There were also some other projects by local and OTCE architects. During the Franco period many schools were build following the so-called Plan Tena model-projects.KeywordsState Schools’ Architecture, 19 th and 20 th Centuries, Terán Schools, Foundations, Indianos (Spanish emigrants to Latin America who returned to Spain having made a fortune), Jándalos (people from Cantabria who emigrated to Andalusia seeking to make a fortune), County Architect Alfredo de la Escalera, Council Architects, OTCE, Model-Projects.